AN ASSESSMENT OF SERBIAN INTERNATIONAL SUNFLOWER OIL TRADE - Titin, Sanja; Popović, Rade; Matkovski, Bojan (Economics of Agriculture, 2025)
The objective of this study is to assess Serbia’s international market position in the sector of sunflower derivatives and edible fats from 2014 to 2023, with particular focus on competitiveness and stability as global trade partner. Using method Revealed Comparative Advantage (RCA) and calculating the Self-Sufficiency Ratio (SSR) the study evaluates Serbia competitiveness and its ability to meet domestic needs through domestic production. The analysis covers key products such as margarine, sunflower seeds, and sunflower oil (both crude and refined). Over the past decade Serbia has experienced significant growth in production and export of sunflower based products, particularly in category of refined oil. Sunflower industry stands out as a stable partner in the global market of sunflower products, following price dynamics and adapting to market challenges. The findings of this research provide a foundation for further discussion on measure to enhance Serbia’s competitiveness, with an emphasis on adapting to global market changes and challenges.